Pengaruh Kesesuaian Kualitas Produk Terhadap Kepuasan Konsumen Skincare Dengan Iklan Influencer Tasya Farasya - Nabila Keysha Mutmainah; Dwi Septianingrum; Laila Fitria; Fawwaz Akif Prayoga; Arsyadona Arsyadona (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study was conducted to understand the relationship between the suitability of product quality and influencer advertising by Tasya Farasya on consumer satisfaction with skincare products. A quantitative approach was used, employing the Chi-Square test method to examine the significance of the relationship between two categorical variables: product quality suitability (suitable or not suitable) and consumer satisfaction (satisfied or not satisfied). The primary data was obtained through a survey distributed to 30 consumers of skincare products who follow influencer Tasya Farasya on social media. The analysis results show a strong correlation between product quality suitability and the level of consumer satisfaction. When the product quality meets expectations, consumers tend to experience higher satisfaction. The Chi-Square test resulted in a significance value of 0.004, which is lower than 0.05, indicating a significant effect. Both variables show a notable relationship. From the analysis, it can be concluded that the quality of products promoted by influencers plays an important role in shaping consumer perception, and consumer satisfaction is influenced by the quality of the skincare products they use.